ABBREVIATIONS FOUND IN THE STOCK INFORMATION COMMUNITY IN THE WHATSAPP CHAT GROUP MIRAE ASSET OE WEST SUMATERA: A MORPHOLOGICAL STUDY - Malina, Adilla Okta; Reniwati, Reniwati; Usman, Fajri (STBA Prayoga Padang, 2023)
ABSTRACT Developing abbreviations are not only found in the field of linguistic sciences but also in the field of economics, such as found in the communities in the WhatsApp group. This study aims to classify any abbreviation found in the information community within the WhatsApp Mirae Asset Group OE, West Sumatera. Then, the process of forming the abbreviation available in the information community stock in the WhatsApp Group Mirae Asset OE, West Sumatera. There are three stages in the study, that's the collection stage and the supply of data, the data analysis stage, and the presentation phase of data analysis. At the data supply stage used Sudaryanto. Sudaryanto used a method of gathering data using listening methods and tap techniques, It is called a basic technique. In advanced techniques, SBLC techniques (involuntary-free litigation-free) only listen to the use of language without being involved in the process of language use without getting involved. Next, followed by note technique. At the data analysis stage, the method used is the solid method of Sudaryanto. By determining tool used a referral method that has two techniques, It's a basic sorting technique of intralingual PUP, the HBB technique, and the equating technique (HBS). Data analysis methods and techniques used formal and informal methods set out by Sudaryanto. Data analysis found four types of improvisation. Which is; an abbreviation, partition, acronym, and a symbol of letters. Abbreviation found 13 data, section found 7 data, acronym found 12 data, and the symbol a letter found 9th letter of data. In the formation process, the formation of the abbreviation process abbreviated 13 data, the 7th part of the data, 12 data acronyms, and the 9th letter of data. There was a process that wasn't exposed by the previous theory, It's the merge of shortness, the principle that was described by Kridalaksana.